THE EFFECT OF EARNING PER SHARE, PRICE EARNING RATIO, PRICE TO BOOK VALUE ON STOCK RETURN IN THE INDONESIA STOCK EXCHANGE - Silaban, Feliks Manihar; Yanto, Ery; Cakranegara, Pandu Adi (Lentera Ilmu Madani, 2024)
This research is aimed to answer the effect of Earnings per Share, Price Earning Ratio, Price to Book Value on stock return. The total sample use 228 manufacture companies listed in Indonesia Stock Exchange for period 2019-2021. Dependent variable in this research is stock return, while Earnings per Share, Price Earning Ratio, Price to Book Value as independent variables. Sample was selected using purposive sampling method. This research used Multiple Regression Analysis as a method of data analysis. Based on the results of testing and analysis of data, found that the partial Earnings per Share has a negative effect on stock returns, Price Earning Ratio has a negative effect on stock return, Price to Book Value has a positive effect on stock return while simultaneously Earnings per Share, Price Earning Ratio, Price to Book Value have effect to stock return.